Phase II/III weekly nab-paclitaxel plus gemcitabine or carboplatin versus gemcitabine/carboplatin as first-line treatment of patients with metastatic triple-negative breast cancer (the tnAcity study): study protocol for a randomized controlled trial. Issue 1 (December 2015) - Yardley, Denise; Brufsky, Adam; Coleman, Robert; Conte, Pierfranco; Cortes, Javier; Glück, Stefan; Nabholtz, Jean-Mark; O'Shaughnessy, Joyce; Beck, Robert; Ko, Amy; Renschler, Markus; Barton, Debora; et al.
Abstract Background Triple-negative breast cancer is an aggressive disease with unmet clinical needs. In a phase III study of patients with metastatic triple-negative breast cancer, first-line gemcitabine/carboplatin resulted in a median progression-free survival of 4.6 months.nab -Paclitaxel-based regimens (with gemcitabine or carboplatin ± bevacizumab) also demonstrated efficacy and safety in first-line phase II trials of human epidermal growth factor receptor 2-negative metastatic breast cancer. Trial design In this international, multicenter, open-label, randomized phase II/III trial, the efficacy and safety of first-linenab -paclitaxel with gemcitabine or with carboplatin will be compared with gemcitabine/carboplatin (control arm) for metastatic triple-negative breast cancer. Methods In the phase II portion, 240 patients with measurable metastatic triple-negative breast cancer and treatment naive for metastatic disease will be randomized 1:1:1 (stratified by disease-free interval: ≤ 1 versus > 1 year) tonab -paclitaxel 125 mg/m2 plus gemcitabine 1000 mg/m2, nab -paclitaxel 125 mg/m2 plus carboplatin area under the curve 2 mg × min/mL, or gemcitabine 1000 mg/m2 plus carboplatin area under the curve 2 mg × min/mL, all given on days 1 and 8 of a 21-day cycle. Investigator-assessed progression-free survival (primary endpoint), overall response rate, overall survival, and safety will be assessed. A ranking algorithm of five efficacy and safety parameters will be used to pick the "winner" of thenab -paclitaxel regimens. In the phase III portion, 550 patients will be randomized 1:1 (stratified by disease-free interval: ≤ 1 versus > 1 year, and prior adjuvant/neoadjuvant taxane use) to thenab -paclitaxel combination arm selected from the phase II portion or to the control arm. Patients in phase II will not be part of the phase III population. The phase III primary endpoint is blinded, independently-assessed progression-free survival; secondary endpoints include blinded, independently assessed overall response rate, overall survival, disease control rate, duration of response, and safety. Biomarker and circulating tumor-cell exploratory analyses and quality-of-life assessments will also be performed. A list of approving ethical bodies was provided in Additional file 1. Discussion The tnAcity trial aims to identify a new standard cytotoxic chemotherapy regimen for first-line treatment of metastatic triple-negative breast cancer. Trial registration ClinicalTrials.gov:NCT01881230 . Date of registration: 17 June 2013.